Uniqueness theorem for sequences of piecewise polynomial functions - Keryan, Karen (Armenian Journal of Mathematics, 2017)
In the paper sequences of piecewise polynomial functions are considered, where each of the function is the projection of subsequent ones. A reconstruction theorem is proved for such sequences converging in measure from its limit if the majorant of the sequence satisfies some condition..
Keywords: piecewise polynomials; uniqueness; majorant; AH-integral